New products of future potential in the Philippines cassava flour and grates - Loreto, Alan B.; Orias, Ramón R. (International Center for Tropical Agriculture, 2001)
In most parts of the Philippines, root crops have evolved from being mainly a source of energy-rich human food to a key commercial crop with high-value and marketable products in the form of flour and grates. Economic analysis indicates that cassava flour could be competitive, both in price and quality, with wheat flour. Allowing a 25% profit margin attained from production to processing, cassava flour may be sold at 75% the cost of wheat flour. This resulted in a reduction of 5% in the cost of bread using a composite flour mix of 80% wheat and 20% cassava. It also produced a special type of aroma, texture and distinct taste, especially if using the Golden Yellow variety released by the Philippines Root Crops Research and Training Center (PRCRTC; now renamed PhilRootcrops). Cassava grates, on the other hand, is the main component of high-value food products like cassava cake, “pitsi-pitsi” and cookies. Initial studies indicate its wide acceptability in urban markets, resulting in increasing demand. It obtained a return on investment (ROI) of 50%, compared to cassava flour, which had only 20%. Both products have their own processing system and equipment developed by PhilRootcrops, the Univ. of the Philippines in Los Baños (UPLB), and a private manufacture, the ALMEDA. These plants have served as pilot projects in previous studies. The economic impact can only be felt if these village-type plants go into commercial production with sufficient and sustained volume. As the demands for flour and grates grow, there should be a number of these village-type plants in each cassava production area. Moreover, research and development on system improvement and evaluation should be continuously pursued with full integration of all efforts from crop production to product development.